Enhanced paracetamol removal using PES/GO mixed matrix membranes: A study on synthesis, characterization, and performance evaluation - Ntone, Ellora Priscille Ndia; Sunarti, Abd Rahman; Rozaimi, Abu Samah; Alsalhy, Qusay F. (Elsevier B.V., 2024)
This research outlines the adsorptive performance of PES/GO-based mixed matrix membranes in the adsorption of paracetamol. Four different concentrations of GO (0, 0.1, 0.4, and 0.5 wt%) were added to the PES polymer solution using the phase inversion method. Characterization of membranes, like Fourier transform infrared (FTIR) spectroscopy, scanning electron microscope (SEM), and atomic force microscopy (AFM) probe, contact angle, and mechanical properties were performed on the membranes produced. Permeability, paracetamol rejection and flux recovery ratio were also performed. The membrane chemical, morphology, and pore structure were improved after GO was added. GO also upgraded the hydrophilicity of the membranes. In addition, the presence of GO increased the permeability of the membranes and the rejection of paracetamol at pH 7. MMM PES/GO-0.4 was found to be the best membrane with permeability of 11.61 L/m2 h.bar and rejection of 98.53 %. Besides, equilibrium isotherm and kinetic studies revealed that the Langmuir model offered the best fit for isotherm, while pseudo-second order offered the best fit for kinetic. On the other hand, extreme concentration of GO (0.5 wt%) reduced paracetamol rejection, permeability, and flux recovery ratio. The results imply that GO is a sustainable and effective additive for water treatment, and an optimum amount increases the hydrophilicity and permeability of membranes and also enhances the adsorptive properties of the membrane.